The effects of climate change on developing of freshwater scarcity and conflicts in Hungary - Szalkay, Csilla; Schlanger, Vera (JOURNAL OF LANDSCAPE ECOLOGY, 2004)
There are about a thousand million km3 of water on Earth, but less than 3% of it is fresh. Most of the freshwater (about two-thirds) is locked in ice, so this is not available for ecosystems. Available freshwater (100 000 km3 globaly) is not spread evenly on Earth. In recent years because water quantity in many countries of the World is unsatisfactory freshwater scarcity is developing. Freshwater scarcity of different areas of the World is so serious that it causes national and international conflicts. These conflicts might even lead to violence. Freshwater scarcities and conflicts usually have complex causes because many contextual factors are combined together. Environmental, economic, social, political stresses and climate change have a major effect on developing scarcity by putting pressure on water supplies. Among these factors the most important is climate change in Hungary. Over the last decades because the mean yearly rainfall has decreased serious drought has developed in many areas of the country, especially in the region of Tisza. There have not been any conflicts in Hungary yet, but that might happen in the future. There are some studies into Hungarian climate change which use different scenarios. There are still many unknowns, but by 2100 warmer and drier weather is forecast than at present. As in other countries of the World this could be conducive to developing freshwater scarcity and different kind of conflicts in Hungary.